The Principles of Good Faith in E-Contract Financial Technology - Kusumastuti, Dora; Sutoyo, Sutoyo (JURNAL AKTA, 2024)
This research discusses the Principle of Good Faith in E-Contract Financial Technology, which is a relatively new type of agreement in Indonesia. An e-contract can be formed when there is an agreement or mutual consent between the parties involved in the contract during its drafting. The existence of an e-contract is a new development in modern contract types, requiring appropriate regulation based on clear legal foundations. However, in practice, current regulations are not yet able to fully protect the parties involved in e-contracts. Therefore, in the creation of e-contracts, it is necessary to have a controlling mechanism based on moral values and conscience, commonly known as the principle of good faith, to support the principle of freedom of contract. The principle of good faith is considered the most important (super eminent principle) in contracts. Given the various issues that arise, this research aims to discuss the importance of the principle of good faith in e-contract financial technology. This subject research is E-Contract Financial Technology, method research used is normative juridical, with data sourced from secondary data, analyzed using deductive logic. The research results indicate that the principle of good faith needs to be applied and instilled in the parties involved in the contract, namely business actors, in this case, fintech providers, and consumers as fintech users. This principle ensures that the contract's substance is carried out based on solid trust or confidence, as well as the good will of the parties involved. By applying the principle of good faith to the parties involved, the risk of wanprestatie on the part of any party can be minimized, as there is already a foundation of trust and good will.